GE_GERICHTE A/1469/2003 vom 7. September 2004 - GE Cour de justice (2004)
; AI(ASSURANCE) ; MOYEN AUXILIAIRE ; APPAREIL ACOUSTIQUE ; CONVENTION TARIFAIRE ; MESURE DE RÉADAPTATION(ASSURANCE SOCIALE) ; MESURE DE RÉADAPTATION(ASSURANCE SOCIALE)